Juridical Analysis of the Role of the Indonesian National Police Employment Desk in Handling Labor Issues in Indonesia - Masyithah Azzahrah Warly Putri; Desi Nurliyanti Putri; Agusmidah; Nita Nilan Sry Rezki Pulungan (Mahadi: Indonesia Journal of Law, 2026)
This study aims to examine the role of the Indonesian National Police Employment Desk within the labor law enforcement system and to identify the forms of labor issue handling carried out by the institution. The Employment Desk of the Indonesian National Police can be interpreted as a unit or working system within the Criminal Investigation Agency of the Indonesian National Police that is responsible for receiving complaints, conducting mediation, and enforcing laws related to labor issues. This research employs a normative juridical method using conceptual and statutory approaches. The legal materials used consist of primary legal materials in the form of laws and regulations related to labor and police institutions, as well as secondary legal materials obtained from books, journals, and official publications concerning labor issues and the Employment Desk of the Indonesian National Police. The results of the study indicate that the establishment of the Employment Desk reflects an expansion of the approach to handling labor issues in Indonesia. Labor issues that were previously resolved mainly through labor supervision and industrial relations mechanisms now also involve police institutions, particularly in cases containing criminal elements and the potential to trigger social conflict. In practice, the Employment Desk not only performs law enforcement functions, but also serves as a complaint mechanism, a facilitator for dispute resolution, and a form of assistance for workers affected by labor issues. Therefore, the existence of the Employment Desk demonstrates an effort to strengthen worker protection and maintain industrial relations stability in Indonesia.